2020
DOI: 10.3390/jcm9020436
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Biogenesis, Methods of Isolation and Clinical Application of Human Cellular Exosomes

Abstract: Exosomes are a heterogenous subpopulation of extracellular vesicles 30–150 nm in range and of endosome-derived origin. We explored the exosome formation through different systems, including the endosomal sorting complex required for transport (ESCRT) and ESCRT-independent system, looking at the mechanisms of release. Different isolation techniques and specificities of exosomes from different tissues and cells are also discussed. Despite more than 30 years of research that followed their definition and indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 132 publications
(145 reference statements)
0
101
0
1
Order By: Relevance
“…At present, more researches are on ESCRT-dependent and ESCRT-independent mechanisms. [14][15][16] However, it has recently been reported that certain components, such as four-transmembrane domain proteins and lipid raft, are also involved in the formation of some exosomes. 17,18 Therefore, the exact mechanism remains controversial.…”
Section: Origin and Classification Of Exosomes Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more researches are on ESCRT-dependent and ESCRT-independent mechanisms. [14][15][16] However, it has recently been reported that certain components, such as four-transmembrane domain proteins and lipid raft, are also involved in the formation of some exosomes. 17,18 Therefore, the exact mechanism remains controversial.…”
Section: Origin and Classification Of Exosomes Formationmentioning
confidence: 99%
“…It has strong specificity, high sensitivity, high purity and high yield, and does not set the upper limit of the starting sample volume when based on magnetic beads. 16,58,59 For example, the enzyme-linked immunosorbent analysis technique based on microplates is used to enrich exosomes in fluids such as serum, plasma and urine. Quantitative detection and analysis found that the yield of exosomes harvested by this method is equivalent to that of ultracentrifugation, but the demand of samples is much smaller.…”
Section: Immunoaffinity Chromatography (Iac)mentioning
confidence: 99%
“…The techniques used for EV quantification include protein concentration, nanoparticle tracking analysis, tunable resistive pulse sensing, vesicle flow cytometry, surface plasma resonance, and electron microscopy. There are many recent reviews describing the predominant methods currently being used in the field [11,13,[70][71][72]. The culture conditions and external stimuli of MSCs during EV production can alter the rate of EVs secreted and the EV composition, with resultant changes in the observed effects [17][18][19]73].…”
Section: Therapeutic Development Of Evs For Lung Injury and Diseasementioning
confidence: 99%
“…That may have repercussions on their extraction; for example, isolated exosomes may contain subpopulations with a distinct size range. Therefore, an optimal method for the exosome isolations would require large pools of purification procedures, a high recovery yield, high purity of exosomes, and high efficiency [75]. Several exosomes isolation techniques have been developed, each exploiting a particular property of exosomes, such as their density, shape, size, and unique surface proteins, to aid their isolation [76].…”
Section: Heterogeneity Effects: a Complexity That Conditions The Isolmentioning
confidence: 99%